Continuous-Wave Intracavity Multiple Optical Parametric Oscillator Using an Aperiodically Poled Lithium Niobate Around 1.57 and 3.84 μm - Yongji Yu; Xinyu Chen; Libo Cheng; Shutao Li; Chunting Wu; Yuan Dong; Yuegang Fu; Guangyong Jin (IEEE Photonics Journal)
A continuous-wave 1.57 and 3.84 μm intracavity multiple optical parametric oscillator based on a single MgO:APLN crystal is reported for the first time. The synchronized dual-wavelength laser is obtained by using a folded-type double cavity, which consists of a 1064-nm resonator and a multiple optical parametric oscillator. With T = 10% at 1.47 and 3.3 μm output couplers, maximum output powers of 3.13 W at 1.57 μm and 0.85 W at 3.84 μm are obtained, corresponding to slope efficiencies of 6.8% and 1.9%, respectively. The power stabilities are better than 1.8% and 3% at the maximum output power in half an hour.